Linking fire behaviour and its ecological effects to plant traits, using FRaME in R - Philip Zylstra (Methods in Ecology and Evolution)
Abstract Floral fire ecology incorporates a feedback loop in which plants influence fire behaviour and fire behaviour influences the flora. Recent advances in fire behaviour modelling have quantified many plant‐based drivers of fire behaviour, but the consequent ecological effects of this have not yet been adequately modelled mechanistically. Here, I introduce the Fire Research and Modelling Environment (FRaME) as the open‐source R package frame on GitHub. FRaME calculates the influence of plants on fire behaviour using a biophysical, mechanistic model of fire behaviour, building this into complex simulations. From these, it models heat transfer from flames into surrounding surfaces, calculating its ecological effects on plants and soils. I demonstrate the application of the central analysis functions using a detailed case study, in which I validate predictions of fire behaviour and ecological effects, and derive quantitative measures for the efficacy of different management treatments to mitigate fire risk to a vulnerable ecosystem. FRaME modelling predicted ecological effects such as the breaking of seed dormancy, scorch and the girdling of different tree strata, consistent with observed effects and providing insights into treatment efficacy that were not captured by existing assumptions. FRaME analyses were able to identify treatments that both increased the likelihood of success in containing fires and minimised fire impacts on a fire‐sensitive ecosystem. FRaME provides a platform to examine the full role of fire in an ecosystem, from the ways that biota drive flammability to the influence of that flammability on the ecosystem. By mechanistically incorporating the effect of biophysical drivers throughout this feedback, FRaME can provide novel insights and solutions for complex problems, quantify risk and guide effective mitigation measures. The model is extensible, providing a conceptual framework into which emerging work on flammability and fire effects can be incorporated.